Cooperation and Territorialization in the Production of Health Consortia in Bahia - Vasconcelos Rocha, Carlos; Morais Castro, José Flávio (Journal Studies of Public Policy, 2024)
The objective of this work is to discuss and evaluate the elements that have hampered or facilitated “horizontal cooperation” for the production of public policies in the area of health. Specifically, it aims to analyze the factors that enabled the dissemination of Interfederative Health Consortia in the state of Bahia. Taking institutionalization of federative cooperation as the stabilization of rules and processes, the question that will guide the work is to verify how, over time, the actors, their interests and their problem agendas have influenced inter-municipal cooperation in the production of health policy. Aspects that contribute to cooperation are pointed out. In addition, it seeks to explain the patterns of territorialization of consortia. In this aspect, the path dependence effect proved to have great explanatory power. The work involved bibliographic research, semi-structured interviews and the Geographic Information System (GIS).